CBT in the workplace in Indonesian vocational high school - Budi Santosa; Yusri bin Kamin (Journal of Vocational Education Studies, 2018)
This study aims to describe the competency-based training (CBT) model in the workplace in vocational high school (VHS) in Indonesia. Students of VHS conduct learning in school and at workplace/industry. A good CBT model will produce skilled vocational graduates, which will reduce unemployment. The method used in this study is research and development by Borg and Gall. Research steps include: preliminary study, development, and testing of students, teachers, and industry mentors totaling 79 people. The finding of this research is that the CBT model implemented in the workplace must meet the following steps: (1) the student must have basic skills as stated in the skill passport, (2) the students choose the location of the practice which already has the memorandum of understanding with the school, (3) VHS assigns students to perform industrial work practice according to their approval from industry, (4) competency based assessment can be done through real work, (5) supervisor industry as an external assessor to test students, and (6) competencies that have been mastered by students recorded in skill passport.